On Simulation of Single Electron Transistor - Jain*, A.; Ghosh, A.; Sarkar, S.K. (Asian Journal of Chemistry, 2013)
To explore the single electronics technology efficiently we need a proper simulation environment. In this paper we have investigated three basic simulation methodologies of single electron transistor i.e., Monte carlo, Master equation and spice macro modeling. Basically the analytical modeling of single electron transistors is based on orthodox theory of single electron tunneling. Here we have compared the simulation results of V-I characteristics of single electron transistor obtained from analytical modeling, macro modeling and Monte carlo method.